In vitro drug sensitivity (IDS) of patient-derived primary osteosarcoma cells as an early predictor of the clinical outcomes of osteosarcoma patients - Jeerawan Klangjorhor (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: Early prediction of clinical response to conventional chemotherapy is a significant factor in determining an overall treatment strategy for osteosarcoma. Methods: Cells were extracted from treatment-naïve biopsies from 16 osteosarcoma patients who received a doxorubicin and cisplatin-based neoadjuvant chemotherapy regimen and their sensitivities to doxorubicin and cisplatin were measured as IC50 values. Associations of in vitro drug sensitivity (IDS) levels and clinical outcomes were examined. Results: Primary osteosarcoma cells responded to doxorubicin and cisplatin with IC50 values of 0.088 ± 0.032 µM and 16.7 ± 8.5 µM, respectively. The patients with a non-metastatic phenotype and surviving patients showed significantly lower IC50 values for both drugs. ROC analysis defined the optimal IC50 cut-off values for doxorubicin (IDSdox) and cisplatin (IDScpt) as 0.05 µM (AUC 0.82) and 14 µM (AUC 0.87), respectively. Survival analysis found significantly longer disease-free survival (DFS, n = 14) and overall survival (OS, n = 16) times in the patients with low IDSdox (p = 0.0064 for DFS and p = 0.0102 for OS) and low IDScpt (p = 0.0204 for DFS and p = 0.0021 for OS). Interestingly, when the patients with low IDScpt and those with low IDSdox were combined (Group 1), significant associations with prolonged DFS (p = 0.0042, C-statistic 0.78) and OS (p = 0.0010, C-statistic 0.79) were found. In this cohort, histological response to neoadjuvant chemotherapy could predict only OS. Conclusions: This study indicates that IDS analysis could potentially be a practical, rapid, and reliable technique for predicting clinical outcomes. It could also be used to identify patients for whom conventional chemotherapy is most appropriate and, in the future, help advance personalized therapy.